2023
DOI: 10.1186/s40959-023-00169-y
|View full text |Cite
|
Sign up to set email alerts
|

Detection of right ventricular dysfunction by three – dimensional echocardiography and two - dimensional speckle tracking in breast cancer patients receiving anthracycline- based chemotherapy

Abstract: Background Despite the cardiotoxic effect of anthracycline on the left ventricle (LV) was totally identified. The assessment of the anthracycline effect on the right ventricle(RV) by conventional echocardiography was a challenge due to its complex geometry. We aimed to evaluate the impact of anthracycline on the RV volume and function using 3 dimensional –echocardiography (3DE) and 2 dimensional -speckle tracking echocardiography (2D-STE) in patients with breast cancer. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Similar results were obtained by El-Sherbeny et al that demonstrated early changes in RV function by 3D echocardiography and 2D strain analysis in breast cancer receiving anthracycline chemotherapy A cut-off value of RVRFWLS > 19.3% predicted reduction of LV function. [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained by El-Sherbeny et al that demonstrated early changes in RV function by 3D echocardiography and 2D strain analysis in breast cancer receiving anthracycline chemotherapy A cut-off value of RVRFWLS > 19.3% predicted reduction of LV function. [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…While RV function has not traditionally been a part of the definition of cardiotoxicity, recent evidence indicates that RV abnormalities are prognostically significant in patients undergoing anthracycline and trastuzumab therapy [44]. RV free wall longitudinal strain appears to be an early marker for subclinical RV toxicity, although further validation is needed in clinical trials with longer follow-up periods [45,46].…”
Section: Multimodality Imaging Assessment Of the Different Cardiovasc...mentioning
confidence: 99%